Galectin‐3 Is Associated With Stage B Metabolic Heart Disease and Pulmonary Hypertension in Young Obese Patients. Issue 7 (2nd April 2019) - Gopal, Deepa M.; Ayalon, Nir; Wang, Yi‐Chih; Siwik, Deborah; Sverdlov, Aaron; Donohue, Courtney; Perez, Alejandro; Downing, Jill; Apovian, Caroline; Silva, Vanessa; Panagia, Marcello; Kolachalama, Vijaya; et al.
Abstract : Background: Obesity is a precursor to heart failure with preserved ejection fraction. Biomarkers that identify preclinical metabolic heart disease (MHD) in young obese patients would help identify high‐risk individuals for heart failure prevention strategies. We assessed the predictive value of GAL3 (galectin–3), FSTL3 (follistatin‐like 3 peptide), and NT‐proBNP (N‐terminal pro‐B‐type natriuretic peptide) to identify stage B MHD in young obese participants free of clinically evident cardiovascular disease. Methods and Results: Asymptomatic obese patients (n=250) and non‐obese controls (n=21) underwent echocardiographic cardiac phenotyping. Obese patients were classified as MHD positive (MHD‐POS; n=94) if they had abnormal diastolic function or left ventricular hypertrophy and had estimated pulmonary artery systolic pressure ≥35 mm Hg. Obese patients without such abnormalities were classified as MHD negative (MHD‐NEG; n=52). Serum biomarkers timed with echocardiography. MHD‐POS and MHD‐NEG individuals were similarly obese, but MHD‐POS patients were older, with more diabetes mellitus and metabolic syndrome. Right ventricular coupling was worse in MHD‐POS patients ( P <0.001). GAL3 levels were higher in MHD‐POS versus MHD‐NEG patients (7.7±2.3 versus 6.3±1.9 ng/mL, respectively; P <0.001). Both GAL3 and FSTL3 levels correlated with diastolic dysfunction and increased pulmonary artery systolic pressure but not with left ventricular mass. In multivariate models including all 3 biomarkers, only GAL3 remained associated with MHD (odds ratio: 1.30; 95% CI, 1.01–1.68; P =0.04). Conclusions: In young obese individuals without known cardiovascular disease, GAL3 is associated with the presence of preclinical MHD. GAL3 may be useful in screening for preclinical MHD and identifying individuals with increased risk of progression to obesity‐related heart failure with preserved ejection fraction.